Dampak Globalisasi dan Lahirnya MNCs terhadap Munculnya North-South Development Gap - Jevon Natashya (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2018)
Since the 1980s, the world has changed because of the globalization in every aspect of life. Globalization has some impacts, both in positive and negative. Globalization makes it easier to trade between countries, investment, the expansion of MNCs, low-cost travelling, communications, information access, and other things. Globalization also makes easier for the MNCs to build up their factories and sell their products across the world. But, on the other side, globalization resulted in the development gap between Northern countries (US, UK, Japan, and Australia) and the Southern countries (Latin America, Africa, South Asia, and the others). The impacts mentioned earlier happened because of globalization, which is conducted mostly by the Northern countries that built factories in the Southern countries to push the production cost, get a lot of resources, and cheap labour wages. By the impacts of globalization and the formation of MNCs that led into the North-South development gap, the writer aims to analyze by using the dependency theory on explain about the case as a general.